Immunophenotypic Characterization of Childhood Acute Leukaemia in A Tertiary Care Center of Bangladesh - Ferdousi, Shormin Ara; Md Moslem, Mir Hasan; Nahar, Kamrun; Begum, Rowshon Ara (Dhaka Shishu (Children) Hospital Journal, 2023)
Background: Leukemia is one of the most common tumors in children. Childhood acute leukaemia (AL) is a heterogenous disease. Immunophenotyping is an essential part of the modern diagnostic workup/for typing and subtyping and prognostic stratification of AL and thus for an appropriate treatment of these complex and heterogeneous diseases. Objectives: Objective of this study was to find immunophenotypic charectarization of childhood acute leukemia in children of Bangladesh. There is very limited study done on this subject in our country. Methods: This is a retrospective observational study done in children with acute leukemia under 15 years of age, treated in two tertiary care centers for Paediatric Oncology [Combined Military Hospital Dhaka and Ahsania Mission Cancer Hospital, Mirpur, Dhaka]. Data were collected from hospital registry from 2014 to 2020 and then analyzed. Results: Total study population were 82; among them male 55%, female 45% and M:F 1:0.82. Most common age group was <5 years age with 55% patients. Disease distribution showed 77% patients had ALL and 23% AML. Among ALL, subtype distribution showed B-cell type 90.5% T-cell type 9.5%. A good number of patients did Immuno-phenotyping analaysis before starting chemotherapy, 68 out of 82 acute leukemia patients (83%). In case of B-ALL highest expression of antigen was CD19 (90%) followed by CD10 (76%), HLADR (76%), CD22 (74%), CD79a (68%), TdT (56%) and CD34 (48%). co-expression of CD10/19was seen in 38% cases. Even in 13% cases, expression of myeloid marker CD13 (14%) and T cell marker CD5 (2%) were seen. In case of T-ALL there was 100% expression of CD3. Expression of other antigen CD4, CD5, CD7, CD45, TdT was 33.33% in each. Expression of CD10, CD1a, CD2 and TCRAb also found 33.33% in each. In case of AML highest expression was MPO (93.24%) followed by CD33 (86.58%), CD13 (79.92%), CD117 (73.26%), CD45 (66%), HLADR (46.62%) and CD64 (46.62%). There was 6.66% aberrant expression of B cell marker CD19 and and T-cell marker CD3 (6.66%), CD5 (6.66%) and CD7 (6.66%). Conclusion: In this study we found in case of B-ALL there was maximum expression was CD19 (90%), 2% aberrant expression of T-ALL marker CD5 and 14% aberrant expression of myeloid marker CD13 were present. In case of T-ALL maximum expression was CD3 (100%). In case of AML there was maximum expression of MPO (93%) and CD33 (87%) along with aberrant expression of B cell marker CD19 (6.66%) and 6.66% of each T cell marker CD3, CD5 and CD7 were present. DS (Child) H J 2022; 38(2): 96-102